IL-6 RESPONSES TO GLYCAEMIC INDEX DURING RECOVERY FROM EXERCISE - Hasani, S.H.; Supaporn, S.; Mehranpour, A.B.; Witid, M. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: This study examined the effect of meal with different glycaemic index (GI) on plasma IL-6 concentration and glucose metabolism after maximal lengthening contractions of the knee extensors. Using a cross-over design, Material : 10 healthy males completed 5 sets of 10 lengthening (eccentric) contractions at 120% 1 repetition-maximum. Subjects were randomized to consume the GI beverage (high-GI, low-GI (15% weight per volume; 3 g/kg BM) or placebo in three times within 10 min following exercise, and again at 50 and 110 min during recovery time. Blood samples were collected before exercise and after 0.60, 180 min and 24 h of recovery. Results: Concentration of plasma IL-6 in HGI group was less than LGI and Pla groups. IL-6 tended to significantly increase after exercise in recovery time in 3 groups (all P < 0.05), except for 24 hours (P = 1.00), furthermore there was significant difference for IL-6 between placebo and high glycemic groups in 3hours after exercise (P=.016). Concentration of serum CK in HGI group was less than LGI and Pla groups, CK was significantly elevated at all times points during recovery in 3 groups (all P < 0.05), except for 1 hour after exercise in HGI group (P = 0.31), but there was no significant difference for CK between groups. Conclusion: In summary, consuming HGI carbohydrate during recovery from exercise attenuate plasma IL-6 concentration.